Antimicrobial Activity and DNA/BSA Binding Affinity of Polynuclear Silver(I) Complexes with 1, 2-Bis(4-pyridyl)ethane/ethene as Bridging Ligands. (14th April 2020) - Đurić, Sonja Ž.; Vojnovic, Sandra; Andrejević, Tina P.; Stevanović, Nevena Lj; Savić, Nada D.; Nikodinovic-Runic, Jasmina; Glišić, Biljana Đ.; Djuran, Miloš I.
Abstract : 1, 2-Bis(4-pyridyl)ethane (bpa) and 1, 2-bis(4-pyridyl)ethene (bpe) were used for the synthesis of polynuclear silver(I) complexes, {[Ag(bpa)]NO3 }n (1 ), {[Ag(bpa)2 ]CF3 SO3 . H2 O}n (2 ) and {[Ag(bpe)]CF3 SO3 }n (3 ). In complexes 1–3, the corresponding nitrogen-containing heterocycle acts as a bridging ligand between two Ag(I) ions. In vitro antimicrobial activity of these complexes, along with the ligands used for their synthesis, was evaluated against the broad panel of Gram-positive and Gram-negative bacteria and fungi. The silver(I) complexes 1–3 showed selectivity towards Candida spp. and Gram-negative Escherichia coli in comparison to the other investigated bacterial strains, effectively inhibiting the growth of four different Candida species with minimal inhibitory concentrations (MICs) between 2.5 and 25  μ g/mL and the growth of E. coli, with MIC value being 12.5  μ g/mL. Importantly, complex 2 significantly reduced C. albicans filamentation, an essential process for its pathogenesis. Antiproliferative effect on the normal human lung fibroblast cell line MRC-5 was also evaluated with the aim of determining the therapeutic potential of the complexes 1–3 . The interactions of these complexes with calf thymus DNA (ctDNA) and bovine serum albumin (BSA) were studied to evaluate their binding activities towards these biomolecules for possible insights on their mode of action.